PESAN AL QUR'AN TENTANG PENDIDIKAN - Syaifurrohman, Amir; Lestari, Fina Ailika; Nurrohmah, Nisa (Universitas Aisyah Pringsewu, 2025)
The Qur'an, as a book of revelation that is a guide to life for Muslims, contains various messages and teachings that are relevant to various aspects of life, including education. Education from the perspective of the Qur'an is not only limited to the transfer of knowledge, but also includes the formation of character and morals. Education from the perspective of the Qur'an covers various aspects, including science, morals and spirituality. The Qur'an always encourages its readers to always seek knowledge and improve their abilities, this is reflected in the first revelation regarding the command